2005
DOI: 10.1159/000085249
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine Gel versus Combined Topical Anesthesia Using Bupivacaine, Oxybuprocaine and Diclofenac Eyedrops in Cataract Surgery

Abstract: Purpose: To assess the safety and efficacy of two topical anesthesia regimes for cataract surgery. Methods: 21 patients received a combination of 4 times bupivacaine 0.5, oxybuprocaine and diclofenac eyedrops, 18 patients were given a single topical application of lidocaine gel 2%. A single intracameral injection of lidocaine 1% was administered to all subjects. Results: The extent to which the surgeon was bothered by patient motility was graded as low in about two thirds of all procedures. Patients reported l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Similar pain scores were found between groups, although a greater percentage of patients in the tetracaine group required supplemental drops during the procedure to maintain comfort . Several additional studies subjectively measuring patient comfort showed the 2% lidocaine gel was well tolerated and in some cases superior in anesthetic effect compared to other common topical anesthetics . Unfortunately, comparison of these studies to ours proves difficult due to their subjectivity and inability of our patients to communicate pain level accurately.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Similar pain scores were found between groups, although a greater percentage of patients in the tetracaine group required supplemental drops during the procedure to maintain comfort . Several additional studies subjectively measuring patient comfort showed the 2% lidocaine gel was well tolerated and in some cases superior in anesthetic effect compared to other common topical anesthetics . Unfortunately, comparison of these studies to ours proves difficult due to their subjectivity and inability of our patients to communicate pain level accurately.…”
Section: Discussionsupporting
confidence: 63%
“…In human and veterinary patients, 2% lidocaine gel preparations are routinely used to provide local anesthesia in several surgical procedures, including those of the upper airway, dental, urogenital, and gastrointestinal tract. Several studies have also demonstrated its efficacy in providing anesthesia for ophthalmic procedures in nonsedated humans . However, these 2% lidocaine gel preparations are used off label as they are not intended for ophthalmic use.…”
Section: Introductionmentioning
confidence: 99%
“…Eight studies addressed the use of lidocaine gel in cataract surgery, [6][7][8][9][10][11][12][13] 4 in pterygium surgery, [14][15][16][17] 2 in trabeculectomy/Ahmed valve implantation, 18,19 and 1 on phaco/trabeculectomy combination procedures. 20 There were 2 papers on lidocaine gel for intravitreal injection, 21,22 and 1 on vitrectomy.…”
Section: Resultsmentioning
confidence: 99%
“…This most likely indicates that this concentration is the bare minimum that needs to be utilized in order to achieve an analgesic effect within the patients. Although the majority of the studies used a concentration of 2% when treating patients with lidocaine, there were a few studies within the review that utilized lidocaine at concentrations of 1% and 1.5% [ 5 , 8 , 14 - 15 , 24 - 25 , 29 - 30 , 33 ]. This could potentially indicate that different patients have different thresholds to achieve the analgesic effect or that different procedures with variable combination agents require a lower concentration of lidocaine to ensure the safety of the patient.…”
Section: Reviewmentioning
confidence: 99%